2021
DOI: 10.3390/antiox10030475
|View full text |Cite
|
Sign up to set email alerts
|

Auraptene Enhances Junction Assembly in Cerebrovascular Endothelial Cells by Promoting Resilience to Mitochondrial Stress through Activation of Antioxidant Enzymes and mtUPR

Abstract: Junctional proteins in cerebrovascular endothelial cells are essential for maintaining the barrier function of the blood-brain barrier (BBB), thus protecting the brain from the infiltration of pathogens. The present study showed that the potential therapeutic natural compound auraptene (AUR) enhances junction assembly in cerebrovascular endothelial cells by inducing antioxidant enzymes and the mitochondrial unfolded protein response (mtUPR). Treatment of mouse cerebrovascular endothelial cells with AUR enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The anti-inflammatory and antioxidative effects of AUR also increased oocyte maturation and the fertilization rates of oocytes in an in vivo polycystic ovarian syndrome (PCOS) model [27]. AUR inhibited ROS generation and enhanced mitochondrial respiration through induction of NRF2 in a Parkinson's disease mouse model [28] and activated antioxidant enzymes and the mitochondrial unfolded protein response, which improves junction assembly in cerebrovascular endothelial cells [29]. AUR also induced hepatic GST and NQO1 by activating the antioxidant response in Nrf2 knockout mice [30].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory and antioxidative effects of AUR also increased oocyte maturation and the fertilization rates of oocytes in an in vivo polycystic ovarian syndrome (PCOS) model [27]. AUR inhibited ROS generation and enhanced mitochondrial respiration through induction of NRF2 in a Parkinson's disease mouse model [28] and activated antioxidant enzymes and the mitochondrial unfolded protein response, which improves junction assembly in cerebrovascular endothelial cells [29]. AUR also induced hepatic GST and NQO1 by activating the antioxidant response in Nrf2 knockout mice [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these components exert various effects. HMF exhibits anti-inflammatory activity, inhibits neuronal cell death, promotes BDNF production, stimulates neurogenesis, improves memory impairment, and exerts antidepressant effects [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]; AUR exhibits anti-inflammatory activity, inhibits neuronal cell death, promotes neurogenesis, and suppresses tau phosphorylation [ 25 , 26 , 27 , 28 , 29 ]. NGI also exhibits anti-inflammatory activity, inhibits neuronal cell death, promotes neurogenesis, suppresses tau phosphorylation, and exerts antioxidant effects [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it was demonstrated that caloric restriction could activate the mtUPR via a miRNA-dependent pathway [ 95 ], and the treatment with statins, such as fluvastatin and rosuvastatin, that inhibit the 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase in the mevalonate pathway, activate the mtUPR since they interfere with mitochondrial electron carriers [ 96 ]. Other compounds that were reported as mtUPR activators are chlorprothixene, an antagonist of the D2 dopamine receptor, auranofin, an antirheumatic agent [ 86 ], as well as auraptene, a natural compound from citrus fruits [ 97 ]. Finally, another antioxidant compound that activates the mtUPR is choline, which promotes the SIRT3-AMPK pathway [ 98 ] ( Table 1 ).…”
Section: Mitochondrial Proteostasismentioning
confidence: 99%